Head-group acylation of monogalactosyldiacylglycerol is a common stress response, and the acyl-galactose acyl composition varies with the plant species and applied stress - Vu, Hieu Sy; Roth, Mary R.; Tamura, Pamela J.; Samarakoon, Thilani Nishanthika; Shiva, Sunitha; Honey, Samuel; Lowe, Kaleb; Schmelz, Eric A.; Williams, Todd D.; Welti, Ruth (My University, 2014)
Formation of galactose-acylated monogalactosyldiacylglycerols has been shown to be induced by leaf homogenization, mechanical wounding, avirulent bacterial infection, and thawing after snap-freezing. Here, lipidomic analysis using mass spectrometry showed that galactose-acylated monogalactosyldiacylglycerols, formed in wheat (Triticum aestivum) and tomato (Solanum lycopersicum) leaves upon wounding, have acyl-galactose profiles that differ from those of wounded Arabidopsis thaliana, indicating that different plant species accumulate different acyl-galactose components in response to the same stress. Additionally, the composition of the acyl-galactose component of Arabidopsis acMGDG depends on the stress treatment. After sub-lethal freezing treatment, acMGDG contained mainly non-oxidized fatty acids esterified to galactose, whereas mostly oxidized fatty acids accumulated on galactose after wounding or bacterial infection. Compositional data are consistent with acMGDG being formed in vivo by transacylation with fatty acids from digalactosyldiacylglycerols. Oxophytodienoic acid, an oxidized fatty acid, was more concentrated on the galactosyl ring of acylated monogalactosyldiacylglycerols than in galactolipids in general. Also, oxidized fatty acid-containing acylated monogalactosyldiacylglycerols increased cumulatively when wounded Arabidopsis leaves were wounded again. These findings suggest that, in Arabidopsis, the pool of galactose-acylated monogalactosyldiacylglycerols may serve to sequester oxidized fatty acids during stress responses.
Keywords: Monogalactosyldiacylglycerols; Acyl-galactose; acMGDG; Stress responses